Daily Variation in Sampled Densities of Ixodes scapularis and Amblyomma americanum (Acari: Ixodidae) Nymphs at a Single Site—Implications for Assessing Acarological Risk. Issue 2 (5th January 2022) - Schulze, Terry L; Jordan, Robert A
Abstract: The public health challenge posed by tick-borne disease (TBD) has increased efforts to characterize the spatial and temporal distribution of ticks and associated pathogens to better focus tick control strategies and personal protection measures. We describe variability in nymphal Ixodes scapularis Say and Amblyomma americanum (L.) density derived from daily drag sampling at a single location in New Jersey over 4 yr and explore how observed differences in daily collections might affect the estimation of acarological risk. We found significant variability in the density of host-seeking nymphs that could suggest substantially different rates of human-tick encounters depending on sampling date, habitat, and ambient weather conditions. The spatial and temporal variability in the distribution of 2 sympatric tick species with different host preferences and questing strategies, suggests that to produce results that are comparable among sites across the area sampled, surveillance efforts may be limited to shorter collection seasons, fewer sites or less sampling effort (fewer plots or fewer visits) per site, and a geographic scope that minimizes the potential temporal and spatial biases indicated here. Our results illustrate that evaluation of models of tick distribution or relative acarological risk based on surveillance data requires a full description of the diversity of habitats sampled and the conditions under which sampling is performed. The array of factors that affect tick host-seeking and that could bias interpretation of sampling results emphasizes the need to standardize sampling protocols and for more caution when interpreting tick sampling data collected over large temporal and spatial scales.